Concept development through the inclusion exclusion approach effects on mathematics understanding and achievement - Catubay,Jenny Jesusa J. (2008)
An alternative-teaching strategy anchored on constructivism - the inclusion-exclusion approach (I-EA) - was designed to determine the effects on Grade 5 students' conceptual understanding and mathematics achievement. A quasi-experimental design, particularly the pretest-posttest control group design, was employed. Results of the analysis showed that the students who were taught the inclusion-exclusion approach achieved higher mean score in the Achievement and Concept Tests suggesting the greater effectiveness of the I-EA in helping students gain knowledge as well as enhancing understanding of mathematical concepts. Varying the teaching strategy by the constructivist approach was recommended to elevate students' achievement and conceptual understanding.